La campagne britannique des video nasties. Paniques, claims-making, risques et politique - Martin Barker (Recherches Sociologiques et Anthropologiques, 2012)
In the early 1980s, a powerful campaign erupted in the United Kingdom which sought to control the production and circulation of pre-recorded videos. In this essay I reconsider the campaign in the light of subsequent debates. Three major paradigms have emerged for understanding campaigns such as this : moral panics ; claims-making ; and risk-management. These three approaches are tested via a re-examination of the video nasties campaign centres, for three unresolved issues : 1. whether analysts should simply seek to describe media scares, or need also to take sides, publicly ; 2. whether we should see media scares as naturally-occurring expressions of tensions, or as purposive attempts to increase levels of emotional response ; 3. how we address the status of claims-makers’ public discourses, and their relations with their “private” intentions. From this account, the essays draws several lessons for researchers : (1) the need to research conflicts between declared and actual motives, private and public rhetorics ; (2) the need to be alert to the cynical management of public presentation, in order to ensure appropriate level of panic ; and (3) the dependence of such campaigns on avoiding the kinds of critical questions which activists are inclined to ask.